Effect of integrated use of fertilizers and organic manures on soil and crop productivity under sugarcane (Saccharum officinarum) based cropping system - SWAMY, K KRAMALINGA; RAJU, D V; RAO, TK MALLIKARJUNA; RAJU, PADMA (The Indian Journal of Agricultural Sciences, 2013)
The effect of integrated use of feltilizers (100, 50 and 0% N and full dose of P and K recommended for each crop in cycle) and organic manures [farmyard manure, sunnhemp (Crotalaria juncea L,), pressmud cake and Cake trash applied to sugarcane plant crop and their residual effect on subsequent crops] on soil fertility, physical properties besiqes productivity of crops grown in crop cycle, sugarcane (Saccharum officinarum L.) plant - sugarcane raloon - gingelly (Sesamum indicum ) - rice (Oryza sativa) was studied. Available nitrogen and phosphorus improved due to integrated use of fertilizers and manures at 100 and 50% nitrogen but depleted when no fertilizers and manures were applied. Though the soil available potash depleted at all levels of fertilization, the extent of depletion was lower under integrated use of fertilizers and manures. The bulk density lowered and infiltration rate, water-holding capacity improved under integrated nutrient management system. Integrated use of fertilizers (100% NPK) and organic manures (cane trash+pressmud cake) resulted in highest cane and sugar production of sugarcane plant and ratoon crop and grain yield of gingelly. However, the residual effect of farmyard manure and 100% NPK resulted in maximum production of rice. Application of 50 N+ 100% p and k. and direct and residual effects of organic manures resulted in sustainable crop production which is nearer to 100% fertilizers alone.